Neovascularization: The Main Mechanism of MSCs in Ischemic Heart Disease Therapy - Shi, Weili; Xin, Qiqi; Yuan, Rong; Yuan, Yahui; Cong, Weihong; Chen, Keji (Frontiers in Cardiovascular Medicine, 2021)
Mesenchymal stem cell (MSC) transplantation after myocardial infarction (MI) has been shown to effectively limit the infarct area in numerous clinical and preclinical studies. However, the primary mechanism associated with this activity in MSC transplantation therapy remains unclear. Blood supply is fundamental for the survival of myocardial tissue, and the formation of an efficient vascular network is a prerequisite for blood flow. The paracrine function of MSCs, which is throughout the neovascularization process, including MSC mobilization, migration, homing, adhesion and retention, regulates angiogenesis and vasculogenesis through existing endothelial cells (ECs) and endothelial progenitor cells (EPCs). Additionally, MSCs have the ability to differentiate into multiple cell lineages and can be mobilized and migrate to ischemic tissue to differentiate into ECs, pericytes and smooth muscle cells in some degree, which are necessary components of blood vessels. These characteristics of MSCs support the view that these cells improve ischemic myocardium through angiogenesis and vasculogenesis. In this review, the results of recent clinical and preclinical studies are discussed to illustrate the processes and mechanisms of neovascularization in ischemic heart disease.